Cultura como desenvolvimento entre os Paresi Kozarini - Silveira, Ema Maria dos Santos (2011)
The proposal of the present study is to get to know and to analyze the building up of the culture notion among the participants of the Paresi Kozarini group in the ethnodevelopment context. The main focus is the ethnographic study, presenting a description of Aldeia Rio Verde (Paresi Indigenous Land), understanding it as a synthesis of historic processes which explains the current moment of Paresi Indigenous group. By using the mentioned methodology, the processes and social relations produced along the contact path of this group with regional-national culture were focused, and how that contact affects the present. The research questions which concern the present study refer to the processes of identification of the researched subjects about themselves and in relation to others. According as almost the totality of the indigenous group we usually know as Paresi, recognize itself as Kozarini, the attention is directed to the manner how they see themselves and how they differ from the other Paresi groups, not indigenous people, and other indigenous groups; and which meanings of the prefix ethno- (which culture elements) they have elected to represent and manage external matters to their culture and society, in the context of discussions about ethnodevelopment